Children’s Literature in Transcarpathian Schools for Teaching English as a Foreign Language - Nagy-Kolozsvári, Enikő; Gordon Győri, János (Central European Journal of Educational Research, 2022)
Since the origins of formal foreign language teaching, literature has always played an important role. Currently, modern language teaching trends suggest starting foreign language learning as early as possible; thus, the use of children’s literature in foreign language teaching is undergoing a revolution. This situation encouraged us to examine the use of children’s literature and the attitude of foreign language teachers to it. This article focuses on primary and secondary school English language teachers in a western county of Ukraine (N = 118). The results of the qualitative research revealed that the teachers’ general attitude to the use of children’s literature is positive; they are aware of their advantages but still avoid using these materials. Most teachers do not apply children’s literature in their foreign language teaching because the school curriculum is too congested and fast-paced, they do not have access to appropriate authentic children’s literature, or they were not taught how to utilize authentic children’s literature during their university years. Results suggest that teachers should be encouraged to use children’s literature, though there is no universal solution. The first suggestion is for schools themselves to support teachers, but it would be a significant step forward if this approach were also to be taken in in-service training.